Ocular hemorrhage secondary to thioguanine‐associated veno‐occlusive disease in a child with acute lymphoblastic leukemia in delayed intensification. (15th December 2019) - Bhunia, Nabanita; Yeager, Nicholas D.; Colace, Susan I.; Buzzaco, Dominic; Bajwa, Rajinder P. S.
Abstract: Hepatic VOD is a potentially fatal complication during stem cell transplantation and is rarely seen in the non‐transplant setting. We report the case of a five‐year‐old boy who presented with visual complaints during delayed intensification phase of treatment for ALL. He was found to have bilateral retinal hemorrhages associated with profound thrombocytopenia due to chemotherapy. VOD was diagnosed based on EBMT criteria and was managed with supportive care. Despite resolution of VOD, his vision progressively deteriorated and resulted in blindness. This case highlights the significance of close monitoring of ALL patients in delayed intensification when they are at risk for developing VOD, the importance of refractory thrombocytopenia as a diagnostic feature and the potential for VOD to manifest with intraocular bleeding.